INTEND II randomized clinical trial of intraoperative duct endoscopy in pathological nipple discharge. Issue 12 (20th September 2018) - Gui, G; Agusti, A; Twelves, D; Tang, S; Kabir, M; Montgomery, C; Nerurkar, A; Osin, P; Isacke, C
Abstract: Background: The majority of lesions resulting in pathological nipple discharge are benign. Conventional surgery is undirected and targeting the causative lesion by duct endoscopy may enable more accurate surgery with fewer complications. Methods: Patients requiring microdochectomy and/or major duct excision were randomized to duct endoscopy or no duct endoscopy before surgery. Primary endpoints were successful visualization of the pathological lesion in patients randomized to duct endoscopy, and a comparison of the causative pathology between the two groups. The secondary endpoint was to compare the specimen size between groups. Results: A total of 68 breasts were studied in 66 patients; there were 31 breasts in the duct endoscopy group and 37 in the no-endoscopy group. Median age was 49 (range 19–81) years. Follow-up was 5·4 (i.q.r. 3·3–8·9) years in the duct endoscopy group and 5·7 (3·1–9·0) years in no-endoscopy group. Duct endoscopy had a sensitivity of 80 (95 per cent c.i. 52 to 96) per cent, specificity of 71 (44 to 90) per cent, positive predictive value of 71 (44 to 90) per cent and negative predictive value of 80 (52 to 96) per cent in identifying any lesion. There was no difference in causative pathology between the groups. Median volume of the surgical resection specimen did not differ between groups. Conclusion: Diagnostic duct endoscopy is useful for identifying causative lesions of nipple discharge. Duct endoscopy did not influence the pathological yield of benign or malignant diagnoses nor surgical resection volumes. Registered as INTEND II in CancerHelp UK clinical trials database (https://www.cancerresearchuk.org/about-cancer/find-a-clinical-trial/a-study-looking-at-changes-inside-the-breast-ducts-of-women-who-have-nipple-discharge ). Abstract : Identifies causative lesion